INCLUSIVE LANGUAGE AND SOCIAL REPRESENTATION OF PEOPLE WITH DISABILITIES IN THE EDUCATIONAL CURRICULUM: A LITERATURE REVIEW FROM A DISABILITY SOCIOLOGY PERSPECTIVE: BAHASA INKLUSIF DAN REPRESENTASI SOSIAL DIFABEL DALAM KURIKULUM PENDIDIKAN: TINJAUAN LITERATUR DARI PERSPEKTIF SOSIOLOGI DISABILITAS - Budi Nurhamidin; Suyadi; Herwan Saleh; Oman Sukmana (SOSIOEDUKASI, 2025)
Education has a central role in shaping a social perspective on diversity, including people with disabilities. However, many educational curricula still present a biased and unempowering representation of people with disabilities. This study aims to examine the inclusive language and social representation of people with disabilities in curriculum documents using a sociology approach to disability. This study was carried out through a qualitative method with a systematic literature review approach. Data sources include scientific articles, academic books, research reports, and policy documents collected from databases such as Google Scholar, Scopus, and DOAJ. The data collection technique was carried out by literature selection based on the keywords of inclusive language. The analysis was carried out thematically and narratively, using the framework of the disability social model, the concept of ableism, and a critical theory approach. The results show that the educational curriculum is still dominated by medical approaches and non-inclusive narratives that place people with disabilities as objects of mercy or burden. The language used tends to stigmatize, reinforce stereotypes, and create symbolic exclusion in the classroom. In addition, the involvement of people with disabilities in curriculum formulation is still very minimal. The conclusions of this study emphasize that equitable and inclusive education can only be achieved through paradigm shifts, the use of empowering language, and equal representation in all aspects of the educational curriculum.